Intercultural dialog through education - Mesić, Milan, sociolog (2008)
The paper presents some basic arguments in favor of intercultural dialog through education. First it raises the qeuestion - what kind of worldview and education has dominated the world till emergence of interculturalism and multiculturalism? Then it discusses the ideas of intarcultural and multicultural education. And finally, suggests the changes in a educational system necessary for implementation of intercultural education.
Projekt MZOS
ENG